2011
DOI: 10.1111/j.1540-6520.2011.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Decision Rights in Franchising Networks: A Property Rights Perspective

Abstract: This paper explains the structure of decision rights in franchising networks using property rights theory. Property rights theory explains the allocation of decision rights based on the importance of intangible assets. We submit that franchisees' fraction of decision rights varies positively with the contractibility of local market assets and negatively with contractibility of system-specific assets. Further, franchisees' less contractible innovation assets impact decision rights allocations more than contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 80 publications
0
52
0
1
Order By: Relevance
“…Applied to an HRM context, responsibility for the management of human resources is typically delegated by the franchisor without much regulation to individual franchisees, despite the common assumption that in franchise systems, virtually every aspect is regulated via contract in order to ensure system-wide standardization (Grünhagen et al 2013). There may be variation between franchise systems as regards the level of franchisee HR autonomy (Grünhagen et al 2013); however, several studies have found that franchisees generally have quite significant HR autonomy in their units 1 Burgers et al 2010;Mumdžiev and Windsperger 2011;Truss 2004;Windsperger 2004). The major reasons for this franchisee HR autonomy are to maintain franchisee satisfaction and motivation (Truss 2004), and to avoid legal risks for the franchisor ).…”
Section: Introductionmentioning
confidence: 99%
“…Applied to an HRM context, responsibility for the management of human resources is typically delegated by the franchisor without much regulation to individual franchisees, despite the common assumption that in franchise systems, virtually every aspect is regulated via contract in order to ensure system-wide standardization (Grünhagen et al 2013). There may be variation between franchise systems as regards the level of franchisee HR autonomy (Grünhagen et al 2013); however, several studies have found that franchisees generally have quite significant HR autonomy in their units 1 Burgers et al 2010;Mumdžiev and Windsperger 2011;Truss 2004;Windsperger 2004). The major reasons for this franchisee HR autonomy are to maintain franchisee satisfaction and motivation (Truss 2004), and to avoid legal risks for the franchisor ).…”
Section: Introductionmentioning
confidence: 99%
“…As for the problems associated with the risk sharing (RS) that must support the parties, franchisors should delegate more decision rights when it is difficult to replicate the intangible resources to reduce opportunistic behavior (free-riding) (Mumdžiev and Windsperger 2011). To reduce the likelihood of the premature termination of the contract (hold-up), a guarantee could be feasible that allows the franchisee to belong to other professional groups or gives territorial continuity to the franchisee to enable collateral activities to be pursued (Chu and Liu 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these policies have been suggested by the literature to be peripheral aspects of business and suitable for delegating to franchisees (Michael 1996;Bradach 1998;Windsperger 2004;Yin and Zajac 2004;Mumdziev and Windsperger 2011;Winter et al 2012;Ater and Rigbi 2015). Moreover, Ater and Rigbi (2015) showed that both policies might serve similar purposes.…”
Section: Franchisor Control Over Pricing and Advertising Policiesmentioning
confidence: 99%